Leadership At The Apex : Politicians and Administrators in Western Local Governments - Mouritzen, Poul Erik (University of Pittsburgh Press, 2002)
Although the relationship between elected officials and appointed executives has often been viewed as a struggle between master and servant-with disagreements as to which group occupies which rol-the authors reveal more interdependence and shared influence than conflict over control.
Keywords: Municipal government.; Leadership.; Municipal officials and employees.; Leadership; Administration municipale.; Fonctionnaires municipaux.; municipal government.; 88.13 local government bodies.; POLITICAL SCIENCE / General; Municipal officials and employees; Municipal government; Leiderschap.; Lokaal bestuur.